Students' and instructors' perception on skills training process - Mora Claramita, Widyandana and Ova Emilia (Berita Kedokteran Masyarakat (BKM), 2005)
Background and objectives: This research is to study the factors related to effectiveness of skills training in the skills laboratory regarding preparation of students' clinical skills competence. Method: Questionnaires containing 9 items in 4 grouped questions with 5 point Likert Scale were distributed to 41 skills-training instructors and 159 fourth year students in July 2005. Result: items of effectiveness of the training, equipment and facilities, instructors' preparation and quality of the training were scored significantly better by instructors then by students (p< 0.05). Item of students' preparation was scored significantly worst by instructors then by students